Diagnóstico del clima organizacional de los servidores públicos en la Dirección del Trabajo y Servicio Público Matriz Loja, de la ciudad de Loja, periodo 2023. - Sarango Salazar., Lisbeth Marina (2024)
The purpose of this research work is to develop a diagnosis of the organizational environment in the Department of Labor and Public Service Matrix Loja in Loja city period 2023, in order to evaluate the organizational climate variable and determine the areas that could benefit from improvements in favor of satisfaction, commitment and performance of public servants. The research as such, adopts a quantitative and qualitative approach, involving the collection of information through surveys and interviews, making use of research methods such as: analytical- synthetic and documentary, thus allowing a comprehensive diagnosis in relation to the five dimensions of organizational climate proposed in the work climate evaluation questionnaire of the author Jimmy Jumbo. It is worth mentioning that thirty-four public servants made up the study population, so that the results showed a score of 68.15; which allows affirming that between 68% and 69% of collaborators perceive that the organizational climate in the institution is at an "Acceptable" level. It should be noted that the most highly valued dimension is that of interpersonal relations, indicating that within the institution the bonds of affinity are positive and that collaboration, companionship, support, friendship and respect influence the construction of a good working environment.